Upaya Preventif Memotong Rantai Penyebaran Virus Covid 19 Melalui Peningkatan Kesadaran Personal Hygine Masyarakat Wilayah Kota Tegal - Izah, Nilatul; Hidayah, Seventina Nurul; Maulida, Iroma; Mutiarawati, Mutiarawati; Rahmita, Rahmita; Asqiya, Dea Hikmatul (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2021)
Corona virus or severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a virus that attacks the respiratory system. This disease caused by a viral infection is called COVID-19. Corona virus can cause disorders of the respiratory system, acute pneumonia, until death. Personal hygiene especially washing hands is the easiest and most effective way to prevent the spread of the covid virus 19. However, people's awareness of getting used to washing hands is still very low, this can be caused by several things including the unavailability of a hand washing area or far from crowds. Covid 19 case monitoring data for Tegal City as of 30 July 2020 ie 270 People in Monitoring (ODP) with all completed monitoring status, for 50 Patients Under Monitoring (PDP) with details of 39 returning and 11 dead, while for confirmed cases Covid 19 for Tegal City residents as many as 4 people. The main target of community service activities is the residents of Tegal City, especially in the West Tegal and Debong Region. The method used in this activity is by providing assistance in the form of a place to do hand washing and basic food provided to the community where in its distribution cooperates with the Debong Health Center and the West Tegal Health Center. Community service activities in a preventive effort to cut the covid 19 distribution chain through the provision of hand washing facilities and distribution of groceries to the community in the Districts of West Tegal and Debong carried out in 2 days namely distribution to the District of Debong on May 8 2020, and for the region West Tegal District on May 9, 2020. The distribution of handwashing and groceries conducted in collaboration with local health centers namely West Tegal Health Center and Debong Health Center, this collaboration activity is intended so that our community service team does not directly face to face and meet with many people in an effort we are to prevent the crowd and in an effort to prevent the spread of the covid virus 19